Dinâmica da circulação atmosférica na região de Maringá - Carfan, Ana Claudia (2005)
The purpose of work is the study the urban climate and to verify the possible existence of heat island in the city. Were analyzed daily data of rainfall and temperature, Climatological Station of Maringá (UEM), Irrigation Technology Center Station (UEM) and SIMEPAR Meteorological Station. For the study of the rainfall frequency, the percentage of days with rainfall were calculated in relation to the total of studied days and through the frequency analyzed, the intensity of precipitation was classified in accordance with a determined class interval emphasizing which of these intervals occurred with more frequency. For the analysis of the trends, calculations of the regression and variable average were used, the monthly graph with the straight line of linear regression and the variable average were made. For the making of the ombrothermic graphs and the evolutions of the maximum and minimum temperatures, the software STATÍSTICA was used. In TVM model through this model, a simulation of wind circulation and temperatures in that area was performed. The result has showed that not significant temperature trend was observed. TVM model presented great similarity with the reality, showing the differences of temperatures between the urban and agricultural areas.